A decision support model for determining sizes of marine protected areas biophysical considerations - Licuanan, Wilfredo Y. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2006)
Marine protected areas (MPAs) have become the de facto tool for the management of coastal fisheries because of the relative ease of their implementation and presumed long-term benefits to both fisher- ies and conservation. However, such benefits may be negated if other interventions and restrictions are not applied, and MPA size and design are inadequate. To help promote good governance practices. a simple graphical Stella@ model for determining MPA size is presented, using data from Tabina, Zamboanga del Sur, Philippines, as a case study. Aside from determining minimum MPA size for supporting fisheries, the model can also determine sustainable levels of catch and effort, and the minimum distance from shore that commercial fleets may operate. The model should afford managers and local officials a better appreciation of aspects of MPA deployment and provide fishery scientists and managers a framework when considering practical applications given the dynamic nature of ecosystem management. Results in Tabina showed that MPA deployments alone are not sufficient to manage coastal fisheries and suggest that the entry of commercial vessels nearer to shore may not be accommodated.